El ciclo de la pasión en el sagrario de la iglesia de Santa María del Río de Castroverde de Campos (Zamora), antigua diócesis de León - Oricheta García, Arantzazu (Estudios humanísticos. Geografía, historia y arte, 1997)
The church of Santa María del Río in Castroverde de Campos (Zamora), beloved at the XVI century to León's diocesis. There, is conserved a reinassance ciborium that showes a iconography based in the Passion of Christ with a lot of concomitances with another pieces carved by the school of Juan de Juni and by Gaspar Becerra in many places of León.